Omega-6 and Omega-3 Intake Ratio in Pulmonary Tuberculosis Patients and Its Correlation with Depression Score - Nabila Fawzia; Wiji Lestari; Fariz Nurwidya; Heidy Agustin; Ammar Abdurrahman Hasyim (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Depression affects 45.19% of pulmonary tuberculosis (TB) patients' adherence to treatment, resulting in increased morbidity and death, medication resistance, and continued disease transmission. This study aimed to examine the relationship between omega-6/omega-3 (êž·-6/êž·-3) polyunsaturated fatty acids (PUFA) intake ratio and depression score in patients with pulmonary TB at Persahabatan National Respiratory Referral Hospital, Jakarta. Methods: This was a cross-sectional study of 99 subjects with pulmonary TB. Data were collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), anthropometric measurements, and the Beck Depression Inventory-II (BDI-II). Results: Correlation analysis used the Spearman test and revealed the ratio of êž·-6/êž·-3 PUFAs intake of 7.78 ± 1.13, the median value of depression score was 9 (10-36). There was no correlation between êž·-6/êž·-3 PUFA intake and depression score (r = 0.063; p = 0.534). Conclusion: There was no correlation between êž·-6/êž·-3 PUFAs intake ratio and depression scores in pulmonary TB patients. This is the first study to examine the correlation between êž·-6/êž·-3 PUFA intake ratio and depression score in pulmonary TB patients.